Postoperative Mycobacterium avium osteomyelitis confirmed by polymerase chain reaction - Weigl, Josef A.; Haas, Walter (European journal of pediatrics, 2000)
An 18-year-old male with Escobar syndrome developed Mycobacterium avium osteomyelitis after corrective osteotomy. After three surgical interventions the infection reappeared a fourth time. Repeated attempts at microbiological diagnosis of the …